Sistem Informasi Akademi Sevima Menggunakan Gofeeder Di Akademi Perhotelan Tunas Indonesia - Faiz Ibrahim, Wanda; Rachmad Saputro, Rizky; Adi Saputro, Wahyu; Haryono, Wasis (CV. Shofanah Media Berkah, 2024)
The Academic Information System (SIAKAD) is an important tool for higher education providers. The reporting process regarding all university activities must be carried out by the organizers to DIKTI periodically every semester. The implementation of SIAKAD within the framework of the Tunas Indonesia Hospitality Academy will be very useful for comprehensive academic data processing, will also guarantee data consistency and validation in addition to technical developments, and will improve type of user mobility for . This research aims to develop a Web-based SIAKAD application that is integrated with the PDDIKTI feeder information system. This application comes with several features such as: Review of student biographical data, Learning Results Information (KHS), filling in the Curriculum Card (KRS), viewing lecture schedules, grade transcripts and grade transcripts in the form of student notifications from university administrators. This research utilizes Restful Web services technology which uses HTTP as a data communication protocol in JavaScript Object Notation (JSon) format and Java programming for mobile applications. The research results show that the application was successfully implemented, making it easier for students to complete the academic process, and each data entry process remains integrated with the PDDIKTI feeder in real time.